Influence of aging treatment on mechanical properties and wear resistance of medium manganese steel reinforced with Ti(C,N) particles - Zhihui Cai; Shangkun Wang; Yanjun Zhou; Jiayi Dong; Lifeng Ma; Shilong Liu (Friction)
Abstract In this study, the hot rolled medium manganese steel containing titanium was solution treated at 1,000 °C and followed by aging treatment at 500, 550, and 600 °C. The influence of aging treatment on mechanical properties and wear resistance of medium manganese steel reinforced with Ti(C,N) particles was investigated. It was found that the matrix of medium manganese steel was austenite. The austenite grain size was refined, and Ti(C,N) particles were precipitated after aging treatment. Compared to that of the as-hot rolled sample, the initial hardness of 500 °C aged sample increased by 9.5% to 312.86 HV, whose impact energy was more than doubled to 148.5 J. As the aging temperature raised to 600 °C, the initial hardness changed slightly. However, the impact energy dropped significantly to 8 J due to the aggregation of Mn at the grain boundaries. In addition, the main wear mechanisms of the samples were fatigue wear and abrasive wear. It was worth noting that 500 °C aged sample exhibited the best wear resistance under a 300 N applied load, whose wear loss was just half of the as-hot rolled sample. The relationship between wear loss and mechanical properties indicated that the wear resistance of medium manganese steel was independent of the initial hardness. The large difference in the wear resistance was predominately due to the outstanding work hardening ability of 500 °C aged sample, whose strengthening mechanisms were contributed from transformation induced plasticity (TRIP) effect, dislocation strengthening, twinning induced plasticity (TWIP) effect, and precipitation strengthening.